Academic learning difficulties faced by elite sports students in Chinese universities and appropriate tutoring strategies - Zhoubao Wei; Jian-Hong Ye (Environment and Social Psychology, 2025)
The purpose of this study was to explore the psychological development of the learning difficulties of elite sports students in Chinese universities, and to identify learning strategies to address these difficulties. By using the snowball sampling method, 15 elite sports students from Chinese universities were selected as research participants. Semi-structured interviews and thematic analysis were used to collect and analyze relevant data. Results showed that the learning difficulties of elite university sports students can be divided into personal factors, school factors, family factors and career factors. In order to help these students better adapt to the combination of learning and training and to overcome their learning difficulties, this study puts forward a set of positive guidance strategies. These strategies include establishing individualized learning programs, providing academic support and guidance, strengthening communication and collaboration between school and family, and providing career planning and development support. Therefore, it is hoped to provide some reference and guidance for the cultivation of elite sports students with personalized comprehensive quality and ability, and to promote the achievement of a better balance in their academic and sports development.